2020
DOI: 10.1589/jpts.32.23
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dynamic standing balance with and without an insole in patients with spastic diplegia cerebral palsy

Abstract: This study examined characteristics of dynamic standing balance, with an without an insole, in patients with spastic diplegia cerebral palsy (CP). [Participants and Methods] This cross-sectional study used a crossover design. Eleven patients with spastic diplegia CP and gross motor levels between I and III with spastic diplegia CP (according to the Gross Motor Function Classification System expanded and revised version) were randomly allocated to either the barefoot or insole groups. The Index of postural stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Conversely, dynamic balance consists of the ability to move the center of pressure (CoP) within the BoS and to move CoP from a BoS to another BoS. 14 The timed unipedal stance test (also referred to as timed single-limb stance, unipedal balance test, one-leg stance test, or one-leg standing balance) is a simple test for measuring individuals' static balance. 15 In clinical research settings, gold-standard measurements for static standing balance are typically conducted in motion labs using force plates, where the CoP sway is registered providing the most accurate assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, dynamic balance consists of the ability to move the center of pressure (CoP) within the BoS and to move CoP from a BoS to another BoS. 14 The timed unipedal stance test (also referred to as timed single-limb stance, unipedal balance test, one-leg stance test, or one-leg standing balance) is a simple test for measuring individuals' static balance. 15 In clinical research settings, gold-standard measurements for static standing balance are typically conducted in motion labs using force plates, where the CoP sway is registered providing the most accurate assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that lateral-wedged and heel-lift insoles had a positive effect by increasing the weight-bearing of the hemiplegic side and bilateral symmetry during standing, but these effects were not felt during ambulation [18,19]. Kusumoto et al confirmed that the insoles combined with a metatarsal pad promoted static and dynamic balance in patients with cerebral palsy [20]. Based on the previously mentioned studies, it was found that the insoles had only one additional modification that had been applied for the correction of lower limb kinematic and kinetic abnormalities in most studies on hemiplegic gait [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Static balance is defined as the ability to maintain the line of gravity (vertical line from the centre of mass) of a body within the base of support (BoS) with minimal postural sway. While, dynamic balance consists of the ability to move the centre of pressure (CoP) within the BoS and to move CoP from one BoS to another BoS ( Kusumoto et al, 2020 ; Reina et al, 2022 ). These assessments are routinely used in sports and clinical settings to identify balance disorders.…”
Section: Introductionmentioning
confidence: 99%